2012
DOI: 10.1589/jpts.24.1319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Combined Treatment of Extracorporeal Shock Wave Therapy (ESWT) and Stabilization Exercises on Pain and Functions of Patients with Myofascial Pain Syndrome

Abstract: Abstract. [Purpose] In order to develop a more effective treatment method for pain and function in myofascial pain syndrome, we examined the effects of ESWT, stability exercises, and combined treatment.[Subjects] The subjects were randomly divided into a stabilization exercise group (n=12), an ESWT (Extracorporeal Shock Wave Therapy) group (n=12), and a combined treatment group (n=12).[Methods] The stabilization exercise group performed shoulder joint stabilization exercises. The ESWT group received ESWT for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 10 publications
2
43
0
Order By: Relevance
“…53,54 Of note, H-ESWT may cause side effects such as permanent tendon damage, whereas low-EFD ESTW (L-ESWT) has a lower therapeutic effect. 55 In our study, none of the patients experienced such side effects.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…53,54 Of note, H-ESWT may cause side effects such as permanent tendon damage, whereas low-EFD ESTW (L-ESWT) has a lower therapeutic effect. 55 In our study, none of the patients experienced such side effects.…”
Section: Discussionmentioning
confidence: 45%
“…Similarly, Ji et al 23 used focused L-ESWT for four sessions in MPS patients and found ESWT to be an effective therapeutic modality with reduced VAS scores and pain threshold (PT). In another study, Cho et al 55 used combined therapy as radial L-ESWT for 12 sessions and stabilization shoulder exercise and found greater improvements in pain and functional scores with combined therapy. In addition, Gur et al 21 used focused H-ESWT and compared three sessions with a single session of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most research in shockwave therapy has focused on understanding the mechanism which results in the establishment of a mechano-sensitive feedback loop between the acoustic impulse and the stimulated cells, and involves specific transduction pathways and gene expression. Taking as valid the Energy Crisis Hypothesis, and considering the mechano-transduction effect of ESWT in other diseases [9][10][11][12][13][14][24][25][26][27][28][29] it could be posited that ESWT in MPS may increase perfusion, promote angiogenesis and alter the pain signaling in ischemic tissues caused by the influx of calcium. On the other hand, recent articles have demonstrated that free nerve endings degenerate after the application of ESWT, and that ESWT produces a transient dysfunction of nerve excitability at the neuromuscular junction, [9][10][11][12][13][14][24][25][26][27][28][29] by bringing about the degeneration of AChR.…”
Section: -14mentioning
confidence: 99%
“…And finally, following a pure mechanistic approach, shockwaves might be able to break-up the Actin-Myosin links, as they are propagating perpendicularly to the sarcomere contractions. [9][10][11][12][13][14][24][25][26][27][28][29] There are evidences of the efficacy of Extracorporeal Shockwave Treatment on Myofascial Pain Syndrome as in the Table 1. Müller-Ehrenberget et al 24 revealed the efficacy of focused ESWT on MPS (Piezoelectric device: Piezo Son100) for alleviating pain in 95% of the 30 patients at 3 months, (800 impulses of energy level:0.04-0.26 mJ/mm2;6 Hz; average 7 treatments, 2 sessions per week) 24 Jeon et al 25 demonstrated that 3 sessions of 1500 pulses of low energy (0.10 mJ/ mm2 ) with focused ESWT (Electrohydraulic: Evotron RFL0300) weekly is as effective as TENS and TP injection on 30 patients with MPS in trapezius muscle, measuring the results in terms of pain (visual analog scale e VAS e and McGill Pain Questionnaire), as well as on the Roles and Maudsley scale.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation